Subchronic Exposure of Tofu Processing Wastewater: Effects on Liver Function and Blood Parameters in Wistar Rats - Pratamawari, Dyah Nawang Palupi; Permatasari, Nur; Widodorini, Trining; Kusteja, Jilan Namira; Salsabila, Naurah Rana Khansa; Kusumaningrum, Novia Ayu (JSMARTech: Journal of Smart Bioprospecting and Technology, 2026)
Tofu is a major soybean-based food in Indonesia; however, the potentially harmful effects of tofu processing wastewater (TPW) in home-based tofu industries have not been elucidated. This study aimed to analyze the potential hazard components (heavy metals) in TPW and the subchronic toxicity effects on liver and blood parameters in rats. Thirty-six adult male Wistar rats were divided into 6 groups (n=6): control group, TPW 1.6 ml/day (A), TPW 3.2 ml/day (B), and TPW 4.8 ml/day (C) for 28 days, respectively. The remaining two groups were assigned to TPW 1.6 mL/day (D) and TPW 4.8 mL/day (E) for 28 days, and were sacrificed 14 days after the last day of TPW administration. Body weight, liver relative weight, serum SGPT and SGOT levels, and blood count analysis were measured using standard methods. Statistical analysis was performed using one-way analysis of variance (ANOVA) with P<0.05, following Tukey honestly significant difference as the post-hoc test. This study found acceptable levels of cadmium (Cd) and lead (Pb) in TPW samples. The administration of oral TPW induced elevation of serum SGPT and SGPT levels as well as alteration of blood count parameters. This study concluded that TPW had minimal toxic effects in rats; however, further investigation into its long-term safety applications is warranted.